Crosstalk between keratinocytes and neutrophils shapes skin immunity against S. aureus infection - Focken, Jule; Schittek, Birgit (Frontiers in Immunology, 2024)
Introduction Staphylococcus aureus (S. aureus) infection of the skin leads to a rapid initial innate immune response with keratinocytes in the epidermis as the initial sensors. Polymorphonuclear neutrophils (PMNs) are the first innate immune cells to infiltrate infection sites where they provide an effective first-line of defense. Previous work of our group showed that in inflamed skin a crosstalk between PMNs and keratinocytes results in enhanced S. aureus skin colonization. Methods In this work, we used an in vitro co-culture model to studied the crosstalk between primary human keratinocytes (PHKs) and PMNs in a sterile environment and upon S. aureus infection. We investigated the influence of PHKs on PMN activation by analyzing PMN lifespan, expression of degranulation markers and induction of proinflammatory cytokines. Furthermore, we analyzed the influence of PMNs on the inflammatory response of PHKs. Finally, we investigated the influence of the skin microbiome on PMN-mediated skin inflammation. Results We show that co-culture of PMNs with PHKs induces activation and degranulation of PMNs and significantly enhances their lifespan compared to PMN cultivation alone by an IL-8 mediated mechanism and, furthermore, primes PMNs for enhanced activity after S. aureus infection. The prolonged incubation with PMNs also induces inflammatory responses in PHKs which are further exacerbated in the presence of S. aureus and induces further PMN recruitment thus fueling skin inflammation. Interestingly, infection of PHKs with the skin commensal S. epidermidis reduces the inflammatory effects of PMNs in the skin and exhibits an anti-inflammatory effect. Discussion Our data indicate that skin infiltrating PMNs and PHKs influence each other in such a way to enhance skin inflammation and that commensal bacteria are able to reduce the inflammatory effect.